Overview of cytokines and nitric oxide involvement in immuno-pathogenesis of inflammatory bowel diseases - Soufli, Imene (World J Gastrointest Pharmacol Ther, 2016)
Inflammatory bowel diseases (IBDs), including Crohn’s disease and ulcerative colitis are complex disorders with undetermined etiology. Several hypotheses suggest that IBDs result from an abnormal immune response against endogenous flora and luminal antigens in genetically susceptible individuals. The dysfunction of the mucosal immune response is implicated in the pathogenesis of IBD. The balance between pro-inflammatory cytokines [tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-8, and IL-17A], anti-inflammatory cytokines (IL-4 and IL-13), and immunoregulatory cytokines (IL-10 and transforming growth factors β) is disturbed. Moreover, evidence from animal and clinical studies demonstrate a positive correlation between an increased concentration of nitric oxide (NO) and the severity of the disease. Interestingly, proinflammatory cytokines are involved in the up-regulation of inducible oxide synthase (iNOS) expression in IBD. However, anti-inflammatory and immunoregulatory cytokines are responsible for the negative regulation of iNOS. A positive correlation between NO production and increased pro-inflammatory cytokine levels (TNF-α, IL-6, IL-17, IL-12, and interferon-γ) were reported in patients with IBD. This review focuses on the role of cytokines in intestinal inflammation and their relationship with NO in IBD.